El fósforo orgánico en suelos tropicales - BORNEMISZA, E. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Organic phosphorus constitutes up to 86 percent of the total phosphorus in some acid soils, and in part, is available immediately to plants. It supplies inorganic phosphorus also, through mineralization. As it is protected by its organic nature to a large extent from fixation and leaching, it is the most important phosphorus reserve in many soils, particularly those of the humid tropics. It is generally determined either by ignition or acid-base extraction methods as the difference between total and inorganic phosphorus. Recently, techniques have been proposed for its direct determination after adsorption by activated charcoal. The mineralization of organic phosphorus is affected by various factors, for example soil temperature, pH, and the previous history of the soil. The practical importance of organic phosphorus is considerable. It constitutes an often neglected reserve of the element. Since its concentration is frequently correlated with crop responses to phosphatic fertilizers, especially in conditions of humid tropics where the determination of soil phosphorus by standard analytical methods has often proved to be unsatisfactory, a better knowledge of this form of the nutrient element is urgently needed.